Evaluation of the subtle effects and oxidative stress response of chloramphenicol, thiamphenicol, and florfenicol in Daphnia magna. (18th February 2019) - Yuxuan, Zhang; Peiyong, Guo; Yanmei, Wu; Xiaoyan, Zhang; Meixian, Wang; Simin, Yang; Yinshi, Sun; Jun, Deng; Haitao, Su
Abstract: Phenicol antibiotics, such as chloramphenicol, thiamphenicol, and florfenicol, are commonly used in the veterinary and aquaculture fields to treat diseases and have frequently been detected in aquatic environments. Nevertheless, there is limited information regarding the effects of phenicol antibiotics on aquatic nontarget species. Thus, the present study aims to investigate the long‐term (21‐d) influence on the reproduction and growth of and the acute (24‐h) oxidative response and tissue damage in the crustacean Daphnia magna after exposure to phenicol drugs, including their environmental concentrations. The results indicate that D. magna exposed to florfenicol are likely to cause more adverse effects than those exposed to chloramphenicol and thiamphenicol over long‐term (21‐d) exposures. Furthermore, changes in biochemical biomarkers such as malondialdehyde (MDA), catalase (CAT), and reduced glutathione (GSH) induced by individual and mixtures of phenicol antibiotics were also observed. Low concentrations of chloramphenicol, thiamphenicol + florfenicol, and chloramphenicol + thiamphenicol significantly increased the MDA levels of D. magna after 24‐h exposures, causing cellular oxidative damage in the animals. In addition, discrepancies between CAT activities and GSH levels were observed, underscoring the need to evaluate multiple indicators of oxidative stress in toxicological studies using D. magna as a model. Environ Toxicol Chem 2019;38:575–584. © 2018 SETAC